Higgs-dilaton cosmology: an inflation-dark-energy connection and forecasts for future galaxy surveys - Casas, Santiago; Pauly, Martin; Rubio, Javier (Physical review, 2018)
The Higgs-dilaton model is a scale-invariant extension of the Standard Model nonminimally coupled to gravity and containing just one additional degree of freedom on top of the Standard Model particle content. This minimalistic scenario predicts a set of measurable consistency relations between the inflationary observables and the dark-energy equation-of-state parameter. We present an alternative derivation of these consistency relations that highlights the connections and differences with the α-attractor scenario. We study how far these constraints allow one to distinguish the Higgs-dilaton model from ΛCDM and wCDM cosmologies. To this end we first analyze existing data sets using a Markov chain Monte Carlo approach. Second, we perform forecasts for future galaxy surveys using a Fisher matrix approach, both for galaxy clustering and weak lensing probes. Assuming that the best fit values in the different models remain comparable to the present ones, we show that both Euclid- and SKA2-like missions will be able to discriminate a Higgs-dilaton cosmology from ΛCDM and wCDM.
Gesehen am 10.12.2020